Finger Painting Revolutionizes Early Childhood Education by Boosting Fine Motor Skills: Finger Painting Merevolusi Pendidikan Anak Usia Dini dengan Meningkatkan Keterampilan Motorik Halus - Husniah, Mufarihun Nuril; Iffatur Rocmah, Luluk (Universitas Muhammadiyah Sidoarjo, 2024)
This classroom action research investigates the efficacy of finger painting activities in enhancing the fine motor skills of 5-6-year-old children at Ittihadul Ummah Ngoro Kindergarten. Conducted over two cycles with 20 students in Group B, the study employs observation, tests, interviews, and documentation for data collection. Results indicate a notable improvement in children's fine motor skills, with average achievements rising from 61% to 78% between Cycle I and Cycle II. The findings underscore the value of integrating sensory-rich, hands-on activities like finger painting into early childhood education to support holistic development and academic readiness. Highlight: Finger painting enhances fine motor skills. Integration of sensory-rich activities in early childhood education. Importance of holistic development for academic readiness. Keywoard: Fine motor Skills, Finger Painting, Early Childhood Education, Sensory-rich Activities, Academic Readiness.